Enhancing sustainability with waste hemp-shive and phase change material: Novel gypsum-based composites with advanced thermal energy storage properties - BOZTOPRAK, YALÇIN (My University, 2024)
This study addresses the rising demand for sustainable construction by introducing composite materials from natural and renewable resources: gypsum, hemp, and phase change materials (PCMs). These materials cater to the growing preference for eco-friendly building solutions. Incorporating hemp enhances sustainability while integrating PCMs into the porous hemp structure ensures adequate thermal energy storage and release without leakage. Firstly, the agricultural waste hemp shives and lauryl alcohol (LA) PCM were mixed to create shape-stabilized hemp/PCM composites. The highest PCM ratio was determined in shape-stabilized composites exhibiting non-leakage properties, which was 45 wt %. These composites were then incorporated into gypsum materials at loadings of 7.5 %, 15 %, 22.5 %, and 35 wt % to produce the final composites. Morphological, thermal, and chemical characteristics of shape-stabilized composites were examined using SEM, TGA, and DSC, while the solar thermoregulation tests assessed the gypsum matrix composites. The phase change temperature of PCM was determined as 20.24 °C with a melting enthalpy value of 224.4 J/g. The hemp/PCM shape-stabilized composites demonstrated an impressive melting enthalpy value of 100.2 J/g, with only a slight reduction to 99.5 J/g after 750 test cycles. When the ambient temperature exceeded 50 °C, the central temperature of the cabins containing PCM composites was found to be at least 4 °C cooler than those containing only gypsum. Conversely, when the ambient temperature dropped to around 20 °C, it was observed that the central temperature of the cabins with PCM composites was approximately 2 °C warmer than those with only gypsum. This study introduces a novel approach to creating environmentally friendly gypsum/hemp/PCM composites for thermal energy storage systems.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Social Sciences and Humanities; Management; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Mühendislik; Ekonomi ve İş; ENERJİ VE YAKITLAR; İŞLETME; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENGINEERING; ECONOMICS & BUSINESS; ENERGY & FUELS; BUSINESS; ENGINEERING, MANUFACTURING; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Genel Mühendislik; Strateji ve Yönetim; Sosyal Bilimler ve Beşeri Bilimler; Endüstri ve İmalat Mühendisliği; Renewable Energy, Sustainability and the Environment; Physical Sciences; General Engineering; Strategy and Management; Social Sciences & Humanities; Industrial and Manufacturing Engineering; Building materials; Energy efficiency; Gypsum; Hemp shives; Phase change material; Thermal energy storage